Fu, Lu, Shou, Xi Theme in Architectural Decorations of Lingnan Guangfu during Qing Dynasty: An Iconological Analysis - Ye, Zhenyan (Journal of Ecohumanism, 2024)
Based on an iconological perspective, this study provides an in-depth interpretation of the unique regional characteristics of the Fu, Lu, Shou, Xi (Blessing, Prosperity, Longevity, Happiness) theme in Qing Dynasty architectural decorations within the Lingnan Guangfu region. This study selected 18 Lingnan Guangfu Qing Dynasty buildings from the 131 cultural relics protection units in the List of National Key Cultural Relics Protection Units in Guangdong Province as the research objects. Combining the cultural characteristics, geographical characteristics, religious beliefs, and folk customs of the Lingnan Guangfu region, this study summarizes its characteristics in four aspects: the expression of regional elements, the composition of narrative elements, the elements of cultural diversity, and the unity of function and decoration. By summarizing the unique regional expressions presented through the element combination features and modes used in the Fu, Lu, Shou, Xi theme in traditional Guangfu architecture, this study provides modern designers with a deeper understanding and more precise expressive pathways for Lingnan decorative elements of the Qing Dynasty, allowing traditional decorative motifs to showcase the charm and vitality of regional culture in modern design.